Evaluation of a Five-Ingredient Herbal Combination in Postpartum Hypertension and Maternal Recovery - Efri Leny Rauf; Fifi Ishak; Zuriati Muhamad; Rosmin Ilham (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Postpartum hypertension represents a persistent contributor to maternal morbidity and mortality across developing regions. This quasi-experimental pretest–posttest study evaluated the efficacy of a five-component polyherbal formulation consist of red ginger (Zingiber officinale var. rubrum), garlic (Allium sativum), lemon (Citrus limon), apple-cider vinegar, and honey in improving hemodynamic stability and postpartum recovery. Sixty-two postpartum women at Prof. Dr. H. Aloei Saboe Hospital, Gorontalo, Indonesia, were equally stratified into hypertensive and normotensive subgroups. Participants ingested 5 mL of the standardized mixture twice daily for six weeks. Weekly monitoring assessed blood pressure, lactation adequacy, lochia characteristics, and uterine involution. Statistical analysis using the Wilcoxon signed-rank and chi-square tests confirmed significant reductions in mean systolic (153.55 ± 9.72 -> 120.32 ± 6.84 mmHg) and diastolic (98.39 ± 7.41 -> 79.68 ± 5.96 mmHg) pressures among hypertensive participants (p < 0.001). No significant variations occurred in lactation (p = 0.209) or uterine involution (p = 0.319), whereas lochia normalization exhibited positive association (p < 0.05). No adverse events were reported. The outcomes substantiate the formulation’s antihypertensive and restorative efficacy via antioxidative and vasodilatory mechanisms. Its safety, affordability, and cultural acceptability demonstrate translational potential as an adjunct in postpartum hypertension management. Further controlled, biomarker-based studies are warranted to validate long-term efficacy and mechanistic precision.